Aesthetic and Functional Outcomes After Superficial Parotidectomy – Comparison of Three Reconstruction Techniques: An Interventional Clinical Study - Askar, Sherif M.; Said, Abd El-Raof; Oraby, Tamer; Khaled, Ibrahim; Megahed, Mahmoud A.; Awad, Ali M. (International Archives of Otorhinolaryngology, 2025)
Preauricular defects is one of the main concerns after superficial parotidectomy. Plastic surgeons have described many filling techniques to overcome the problem.To discuss and compare the esthetic and functional outcomes of three postsuperficial parotidectomy reconstruction techniques: partial-thickness, superiorly based sternocleidomastoid muscle flap, en-bloc fat grafting, and platelet-rich fibrin gel.We included 29 adult patients submitted to reconstruction after superficial parotidectomy by partial-thickness, superiorly based sternocleidomastoid muscle flap, en-bloc fat grafting, and platelet-rich fibrin gel. A subjective evaluation of the overall facial appearance was conducted through a 5-point visual analog scale filled out by the patient, a close relative, and 3 blind staff members.Regarding the visual analog scale, in the comparison between the three groups (at the sixth and the twelfth months), the fat group reported the highest mean for satisfaction (3.4 ± 1.1 and 3.83 ± 0.97 respectively) and showed a highly-significant difference when compared to the sternocleidomastoid muscle flap and the platelet-rich fibrin gel groups (p = 0.0001 and 0.016 respectively).Parotidectomy with immediate reconstruction of the surgical defect with an en-block fat graft provides better esthetic outcomes than sternocleidomastoid muscle flap and platelet-rich fibrin gel after 1 year. The sternocleidomastoid muscle flap and fat techniques resulted in minimal surgical-site morbidity and lower likelihood of developing Frey's syndrome. The fat graft yielded the best degree of cosmetic satisfaction with minimal morbidity. Fat overcorrection is recommended.Level of Evidence: 4
Keywords: superficial parotidectomy; sternomastoid muscle flap; fat graft